Impact of oncogene panel results on surgical management of cytologically indeterminate thyroid nodules. Issue 8 (6th April 2018) - Valderrabano, Pablo; Khazai, Laila; Thompson, Zachary J.; Leon, Marino E.; Otto, Kristen J.; Hallanger‐Johnson, Julie E.; Wadsworth, J. Trad; Chung, Christine H.; Centeno, Barbara A.; McIver, Bryan
Abstract: Background: The impact of oncogene panel results on the surgical management of indeterminate thyroid nodules (ITNs) is currently unknown. Methods: Surgical management of 649 patients consecutively evaluated from October 2008 to April 2016 with a single nodule biopsied and indeterminate cytology (193 evaluated with and 456 without oncogene panels) was assessed and compared. Histological features of 629 consecutively resected ITNs (164 evaluated with and 465 without oncogene panels) were also characterized and compared. Results: Oncogene panel evaluation was associated with higher rates of total thyroidectomy (45% vs 28%; P = .006), and central lymph node dissection (19% vs 12%; P = .03) without increasing the yield of malignancy or decreasing the rate of completion thyroidectomy. Most malignancies (64%), including 83% of those with driver mutation identified, were low‐risk cancers for which a lobectomy could have been sufficient initial treatment. Conclusion: Current oncogene panel results seem insufficient to guide the surgical extent of solitary ITNs.